2021
DOI: 10.3389/fchem.2021.687392
|View full text |Cite
|
Sign up to set email alerts
|

Advanced TexSy-C Nanocomposites for High-Performance Lithium Ion Batteries

Abstract: This study is dedicated to expand the family of lithium-tellurium sulfide batteries, which have been recognized as a promising choice for future energy storage systems. Herein, a novel electrochemical method has been applied to engineer micro-nano TexSy material, and it is found that TexSy phases combined with multi-walled carbon nanotubes endow the as-constructed lithium-ion batteries excellent cycling stability and high rate performance. In the process of material synthesis, the sulfur was successfully embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It has been reported that the Te containing ternary sulfide (Li 2 Te x S y ) species at the SEI acts as a good Li-ion conductor to efficiently distribute the Li-ion flux, leading to a homogenous Li plating and stripping. [51,69] The formation of reaction products between Te and polysulfides can also be confirmed from the Te 3d XPS spectra. Figure S13, Supporting Information, shows the presence of Te 4þ peaks at 574.8 eV on the surface of the SEI, which results from the formation of Li 2 TeS 3 .…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…It has been reported that the Te containing ternary sulfide (Li 2 Te x S y ) species at the SEI acts as a good Li-ion conductor to efficiently distribute the Li-ion flux, leading to a homogenous Li plating and stripping. [51,69] The formation of reaction products between Te and polysulfides can also be confirmed from the Te 3d XPS spectra. Figure S13, Supporting Information, shows the presence of Te 4þ peaks at 574.8 eV on the surface of the SEI, which results from the formation of Li 2 TeS 3 .…”
Section: Resultsmentioning
confidence: 76%
“…It has been reported that the Te containing ternary sulfide (Li 2 Te x S y ) species at the SEI acts as a good Li‐ion conductor to efficiently distribute the Li‐ion flux, leading to a homogenous Li plating and stripping. [ 51,69 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recently, lead-acid and Li-ion batteries have been considered as the two types of the most common energy storage batteries (ESB), showing lower storage efficiency and environmentally hazardous, high-cost, and risky flammable organic electrolytes, respectively, restricting and making them powerless to applications in practical large-scale energy storage applications (LSESA). 6,7 Among the most effective ESS for stationary applications, a special place is occupied by RFB technology, encompassing easy scalability of power density and energy capacity, low self-discharge, long cycle life, and cost efficiency to LSESA. [8][9][10] Relative to the traditional Li-ion ESB storing energy methods such as "rocking-chair type", RFB stores the electrical energy by virtue of the soluble redox couples, converting excess electrical energy to chemical energy and vice versa.…”
Section: Introductionmentioning
confidence: 99%